2005
DOI: 10.1007/s10525-005-0112-4
|View full text |Cite
|
Sign up to set email alerts
|

A Paradox of Parasite Prolonging the Life of Its Host. Pearl Mussel Can Disable the Accelerated Senescence Program in Salmon

Abstract: A unique case is analyzed when the accelerated senescence program (progeria) in salmon (Salmonidae) can be canceled by larval parasite of the gills-freshwater pearl mussel Margaritifera margaritifera. As a result, the maximum age of Salmo fishes hosting the mussel can be as high as 13 years. The mollusk-fish system made it possible to demonstrate that the parasite can inhibit senescence of the host and stimulate nonspecific resistance to stress, i.e., can control longevity. The mussel proved to increase the re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
15
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 8 publications
5
15
0
Order By: Relevance
“…In addition, in the low dose treatment—i.e., when a low dose of cercariae was used in the subsequent infection—fish preinfected with glochidia were more likely to become infected with D. pseudospathaceum than the control fish. The numbers of freshwater pearl mussel glochidia in preinfected fish (~400 glochidia per fish on average) were within the range of glochidia numbers found in natural salmonid populations (e.g., Salonen & Taskinen, ; Ziuganov, ), thereby providing a close biological relevance to the experimental findings.…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…In addition, in the low dose treatment—i.e., when a low dose of cercariae was used in the subsequent infection—fish preinfected with glochidia were more likely to become infected with D. pseudospathaceum than the control fish. The numbers of freshwater pearl mussel glochidia in preinfected fish (~400 glochidia per fish on average) were within the range of glochidia numbers found in natural salmonid populations (e.g., Salonen & Taskinen, ; Ziuganov, ), thereby providing a close biological relevance to the experimental findings.…”
Section: Discussionsupporting
confidence: 71%
“…The latter fish is the exclusive host for freshwater pearl mussel glochidia in many Central European populations (Geist, Porkka, & Kuehn, ; Taeubert & Geist, ). Often freshwater pearl mussel glochidia are considered to have a positive or, at most, a very weak negative effect on the host's health (Ziuganov, Zotin, Nezlin, & Tretiakov, ; Ziuganov, ; but see Taeubert & Geist, ). The latter is perhaps more likely to be true since freshwater pearl mussel glochidia demonstrate more than sevenfold growth in the course of 8–10‐month development on the fish gills with a substantial nutrient transfer from fish to glochidia and a shift in the stable isotope composition during the mussel's development (Denic, Taeubert, & Geist, ).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, according to Vaughn et al (2008), mussels provide physical structure via stabilization and bioturbation of sediments, and these effects support, link and influence multiple trophic levels of fluvial ecosystems. Therefore, the relationship between FPM and their salmonid hosts has occasionally been suggested to be symbiotic rather than parasitic , 2005. Furthermore, Ziuganov (2005) has shown that even the FPM infection may be beneficial for salmonid individuals by strengthening them and helping them to survive from asphyxia and hook wounds with higher probability than the uninfected conspecifics.…”
Section: The Interactions Between the Freshwater Pearl Mussel And Hosmentioning
confidence: 99%
“…Therefore, the relationship between FPM and their salmonid hosts has occasionally been suggested to be symbiotic rather than parasitic , 2005. Furthermore, Ziuganov (2005) has shown that even the FPM infection may be beneficial for salmonid individuals by strengthening them and helping them to survive from asphyxia and hook wounds with higher probability than the uninfected conspecifics.…”
Section: The Interactions Between the Freshwater Pearl Mussel And Hosmentioning
confidence: 99%
“…The glue of large selected long-lived sticklebacks rich in biologically active substance (Ziuganov, 2005) was used in experiments as a wound healing, antistress, and antitumor drug. This biodrug was registered under the name Arktika+ by the Ministry of Health of the Russian Federation.…”
Section: Experimental Animals and Materials Collectionmentioning
confidence: 99%